Concurrent Squamous Cell Carcinoma and Chronic Lymphocytic Leukemia Presenting as an Enlarging Neck Mass. (April 2019) - Bhinder, Prabhjot; Chahin, Michael; Zuberi, Lara
Chronic lymphocytic leukemia (CLL) patients are at an increased risk for developing more aggressive lymphomas via Richter's transformation and of developing secondary malignancies. Despite the known association for secondary cancers, oropharyngeal cancers occur rarely. We present a case of a woman with a history of CLL who presented to our facility via transfer for impending airway compromise. Her initial workup was consistent with CLL; however, biopsies were taken of the neck mass because of its aggressive nature. She was treated with rituximab with good response. Final pathology showed evidence of CLL and tonsillar squamous cell carcinoma (SCC). Direct laryngoscopy and further biopsies yielded a diagnosis of unresectable oropharyngeal SCC. She was to be treated with chemotherapy and radiation for her SCC while holding treatment for CLL. This case demonstrates a rare and unexpected concurrent diagnosis.